Mathematical Modelling of Quorum Sensing and Bioluminescence in Bacteria - Sarangam Majumdar; Suman Datta; Sisir Roy (Institute of Advanced Engineering and Science, 2012)
Different types of Quorum Sensing in Bacteria, both intra-species and inter-species, have been analyzed over the last decade. A number of Mathematical Models has been proposed to explain the process of Quorum Sensing which depends on a threshold concentration of autoinducers (or QSM) reflecting high bacterial density. Stability of the solution of the differential equations of such an intra-species model for Vibrio fischeri is discussed in this paper.